2012
DOI: 10.1159/000343242
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-24 Suppresses the Growth of Vascular Smooth Muscle Cells by Inhibiting H<sub>2</sub>O<sub>2</sub>-Induced Reactive Oxygen Species Production

Abstract: Background/Aim: The abnormal growth of vascular smooth muscle cells (VSMCs) induced by reactive oxygen species (ROS) is considered a major pathogenic process in vascular diseases. Interleukin (IL)-24 specifically inhibits cancer cell growth through the induction of cell cycle arrest and apoptosis. However, the role of IL-24 in ROS-induced VSMC growth has not yet been investigated. Methods: An MTT assay, gene expression analysis, flow cytometry and a scratch wound healing assay were performed to determine the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…3A). Our results are also supported by the recent reported observation that recombinant human IL-24 protein induced a cell cycle arrest at the G 0 /G 1 phase through the downregulation Cyclin D1 in MOVAS cells [51]. Together, these data indicate that the downregulation of Cyclin D1 is caused, at least partially, by SC144-induced upregulation of IL-24, and results in cell cycle arrest.…”
Section: Sc144 Causes Cell Cycle Arrestsupporting
confidence: 91%
“…3A). Our results are also supported by the recent reported observation that recombinant human IL-24 protein induced a cell cycle arrest at the G 0 /G 1 phase through the downregulation Cyclin D1 in MOVAS cells [51]. Together, these data indicate that the downregulation of Cyclin D1 is caused, at least partially, by SC144-induced upregulation of IL-24, and results in cell cycle arrest.…”
Section: Sc144 Causes Cell Cycle Arrestsupporting
confidence: 91%
“…Ectopic expression of Bcl-2 and Bcl-XL inhibited Ad-IL24 induced mitochondrial changes, ROS production and apoptosis, which further substantiates the involvement of mitochondrial dysfunction in Ad-IL24 induced apoptosis [41]. In contrast to these findings, Lee et al reported IL-24 inhibited hydrogen peroxide (H 2 O 2 ) induced ROS production in normal vascular smooth muscle cells (VSMC) by reducing mitochondrial H 2 O 2 production and by enhancing the expression of antioxidant enzymes [46]. It is evident from these reports that IL-24 selectively induces ROS-mediated cell death in tumor cells but not in normal cells.…”
Section: Reviewmentioning
confidence: 75%
“…This research suggested that IL-24 may be a potential therapeutic agent in the calcification of VSMCs. Beides this, another study demonstrated that IL-24 suppressed the growth of normal VSMCs by inhibiting H 2 O 2 -induced ROS production through the regulation of mitochondrial ROS production and the expression of antioxidant enzymes ( 44 ). In a recent study, the researchers found that IL-24 polymorphisms were associated with cardiometabolic parameters and cardiovascular risk factors ( 45 ).…”
Section: Discussionmentioning
confidence: 99%